Functional insights into the cellular response triggered by a bile-acid platinum compound conjugated to biocompatible ferric nanoparticles using quantitative proteomic approaches. Issue 28 (6th July 2017) - Díez, Paula; González-Muñoz, María; González-González, María; Dégano, Rosa Ma; Jara-Acevedo, Ricardo; Sánchez-Paradinas, Sara; Piñol, Rafael; Murillo, José Luis; Lou, Gustavo; Palacio, Fernando; Almendral, María Jesús; Millán, Ángel; et al.
Abstract : Bioferrofluids are powerful tools in the biomedical field. Abstract : At present, bioferrofluids are employed as powerful multifunctional tools for biomedical applications such as drug delivery, among others. The present study explores the cellular response evoked when bile-acid platinum derivatives are conjugated with bioferrofluids by testing the biological activity in osteosarcoma (MG-63) and T-cell leukemia (Jurkat) cells. The aim of this work is to evaluate the biocompatibility of a bile-acid platinum derivative conjugated with multi-functional polymer coated bioferrofluids by observing the effects on the protein expression profiles and in intracellular pathways of nanoparticle-stimulated cells. To this end, a mass spectrometry-based approach termed SILAC has been applied to determine in a high-throughput manner the key proteins involved in the cellular response process (including specific quantitatively identified proteins related to the vesicular transport, cellular structure, cell cycle, biosynthetic process, apoptosis and regulation of the cell cycle). Finally, biocompatibility was evaluated and validated by conventional strategies also (such as flow cytometry, MTT, etc .).